Analysis of Meteorological Service Effect of a Low-cloud and Low-visibility Weather Process at Shanghai's two Airports. Issue 2 (May 2021) - Ma, Li; Wei, Xiaodong; Zhou, Xiaoning
Abstract: The emergence of low-cloud and low-visibility can affect air activities, and bring huge economic losses to airlines. Based on the aviation meteorological observation, forecast and airport alert of Pudong and Hongqiao airports, this paper analyses the meteorological service effect of a low-cloud and low-visibility weather process in Shanghai from January 27th to 28th, 2016. The results show that: (1) The absolute error between forecast and actual situation of Pudong and Hongqiao airport presents an obvious normal distribution and the forecast accuracy of Pudong is higher than that of Hongqiao. (2) For the airport with cloud ceiling of 30m∼60m and prevailing visibility of 600m∼800m, the alert of Pudong airport is more accurate and advanced, but for the airport with cloud height of less than 30m and prevailing visibility of 400m∼600m, the airport alert is quite different from the actual situation, and lacks lead time. (3) The alert of Hongqiao airport is accurate for the airport with visibility less than 800m from 03:30 to 10:30 on 28th, and the lead time is relatively high. However, it lacks the lead time for the airport with prevailing visibility greater than 1000m at 11:00 on 28th.